Electroanatomical mapping–guided left bundle branch area pacing in patients with structural heart disease and advanced conduction abnormalities. Issue 3 (30th December 2022) - Richter, Sergio; Gebauer, Roman; Ebert, Micaela; Moscoso Ludueña, Cathleen; Scheller, Dominik; Lucas, Johannes; König, Sebastian; Paetsch, Ingo; Hindricks, Gerhard; Döring, Michael
Abstract: Aims: Left bundle branch area pacing (LBBAP) can be technically challenging and fluoroscopy-intense. Three-dimensional electroanatomical mapping (EAM) facilitates non-fluoroscopic lead navigation and electrogram mapping. We sought to prospectively evaluate the feasibility, safety, and outcomes of routine EAM-guided LBBAP in patients with structural heart disease (SHD) and advanced conduction abnormalities. Methods and results: Consecutive patients with SHD and conduction abnormalities who underwent an attempt at EAM-guided LBBAP were included. The feasibility, safety, procedural, and mid-term outcomes were evaluated. Electrical, echocardiographic, and clinical parameters were assessed at implantation and last follow-up. Thirty-two patients (68 ± 18 years; 19% female) were included, of which 75% had intrinsic QRS > 150 ms, 53% left bundle branch block, and 25% right bundle branch block. Primary EAM-guided LBBAP was successful in 29 patients (91%). The procedural duration was 95 (70–110) min, total fluoroscopy time 0.93 (0.40–1.73) min, and total fluoroscopy dose 35.4 (20.5–77.2) cGy cm2. Paced QRS duration (QRSd) was significantly shorter than intrinsic QRSd (121.9 ± 10.7 vs. 159.2 ± 34.4 ms; P < 0.001) and remained stable during the mean follow-up of 7.0 ± 5.9 months. The LBBAP capture threshold was 0.57 ± 0.23 V/0.4 ms at implantation and remained low during follow-up (0.58 ± 0.18 V/0.5 ± 0.2 ms; P = 0.877). Overall left ventricular ejection fraction improved significantly from 44.2 ± 14.3% at baseline to 49.4 ± 13.1% at follow-up ( P = 0.009), New York Heart Association class from 2.4 ± 0.6 to 1.8 ± 0.6 ( P = 0.002), respectively. No complications occurred that required intervention. Conclusion: Routine near-zero fluoroscopy EAM-guided LBBAP can safely be performed in patients with SHD and advanced conduction abnormalities with high success rates and favourable mid-term outcomes. Further studies are needed to investigate whether the use of EAM improves the overall outcome of conduction system pacing and to identify specific patient populations who benefit the most from EAM-guided lead implantation.